İstanbul Kent Müzesi için yeni yaklaşımlar - Aytokmak, Deniz (My University, 2006)
ABSTRACT The treatise champions the necessity to form a project for a city museum whichis oriented towards the societal education in order to offer the consciousness of being acity-dweller as well as all the cultural components pertaining to the city.In line with the determination for the needs, previously applied projects or theones in process will be dealt according to their aims and strategies, and theirinadequacies and competences will be manifested. Since all the issues related to the cityhas a potential to become a museum, the necessity of making certain definitions andlimiting the convenience of the applications has arisen. Therefore, the goal pursued is toinitially make the right definitions and developing a project according to the needs. Thefunctions that must be available at the planned city museum starting with the existingdefinitions, and the similarities and the differences of the functions which we aim willbe manifested. At this stage, similar examples in Türkiye and available examples in theworld will be compared.For the progression of the aimed identification and memory periods, thecomponents and potential associates for a city museum will be established, and for thispurpose a detailed inventory of all available institutions and establishments that mightprovide material will be prepared. In addition, all similar attempts relating to the city, aswell as the notion of a city museum will be examined and their objectives, applications,and shortcomings that need to be eliminated will be established. At this stage, theobjective is to determine the potential effects of the city museums in instituting theconsciousness of being a city-dweller, and analyzing the projects that have beendeveloped in the issue of eliminating the identification problems by means of socialcultural areas. The shortcomings of the applied projects will be determined as a result ofthis analysis, and will be referenced to the proposal at the final chapter.At the final stage a new proposal will be made, and in order to communicatewith the people who try to become a city-dweller and considering the currentlyavailable sources, a central point will be selected, with the references foreseen to begiven from this center, the necessity of forming satellite-unit museums at theneighborhoods and their potential inclined to cultural tourism will be dealt. Movingfrom this point on, for the city of Istanbul, the identification on individual basis, socio-cultural requirements inclined towards the memory and state of belonging, thecapability of the society to respond to the aimed application, the true state of theproject?s structure, its objective, organization schedule, strategic development,applicability, cadre members for the need, budget, minimal and maximal areas of themuseum to be at the central point and its satellites will be established.As a conclusion, the objective is to develop a project that is anticipated to reacheach and every individual to gain the consciousness of being a city-dweller, forming acity museum at a central point by stipulating the benefits for the cultural tourism,establishing the least and the utmost standards of those satellite/unit museums whichwill be visited by as directed by these centers, and the advantages of such project?seconomical and social yield.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2006
Keywords: Kent müzeleri; APİKAM; İstanbul Şehir Müzesi